The seen and unseen: the unintended impact of a conditional cash transfer program on prenatal sex selection - Sayli Javadekar; Kritika Saxena (Journal of Population Economics, 2025)
This study examines the unintended consequences of the Janani Suraksha Yojana, a conditional cash transfer program in India, on prenatal sex-selective behaviour within a son-preference culture. This program unintentionally altered existing trends in prenatal sex selection through its simultaneous provision of cash incentives to households and community health workers as well as access to prenatal sex detection technology such as ultrasound scans. Using difference-in-differences and triple difference estimators we find that the program causes an increase in the likelihood of female births. Furthermore, we observe a rise in under-5 mortality for girls born at higher birth orders, suggesting a shift in discrimination against girls from prenatal to postnatal. Our calculations suggest that the net impact was approximately 300,000 girls surviving in treated states between 2006 and 2015. Finally, we find suggestive evidence that the involvement of community health workers in facilitating the program is a key driver of this trend. Overall, this study sheds light on the complex interplay between policy interventions, cultural norms, and gender disparities in shaping demographic outcomes.
Keywords: J13; J16; J18; 330; Prenatal sex selection; Missing girls; Sex-selective abortions; Community health workers; Janani Suraksha Yojana